2023
DOI: 10.3390/agronomy13051307
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionizing Maize Crop Productivity: The Winning Combination of Zigzag Planting and Deep Nitrogen Fertilization for Maximum Yield through Root–Shoot Ratio Management

Abstract: Maize is the staple food of China, produced on 33.6% of the total arable land. In this context, an effective strategy to enhance maize yield is essential to meet the demand without expanding the cultivation areas. Maize yield can be increased by two key measures: plant-row space optimization and nutrient management. However, in traditional maize cultivation practices, fertilizer utilization by plants is inefficient. We therefore performed a manipulative experiment over two years (2018–2019), applying four trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that changing the type of urea, such as applying slow-release urea or controlledrelease urea, is of great significance in promoting the efficient use of nitrogen by crops and reducing nitrogen loss [64]. Zheng et al [8] found that the mixed application of urea and nitrification inhibitors or urease inhibitors during summer maize production by dryland farming in the Loess Plateau region of China significantly reduces nitrous oxide and ammonia volatilization, improves the nitrogen use efficiency, and reduces Nr loss, thereby decreasing NF, which also provided inspiration for our subsequent research.…”
Section: Deep Fertilization Decreased Nitrogen Footprintmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that changing the type of urea, such as applying slow-release urea or controlledrelease urea, is of great significance in promoting the efficient use of nitrogen by crops and reducing nitrogen loss [64]. Zheng et al [8] found that the mixed application of urea and nitrification inhibitors or urease inhibitors during summer maize production by dryland farming in the Loess Plateau region of China significantly reduces nitrous oxide and ammonia volatilization, improves the nitrogen use efficiency, and reduces Nr loss, thereby decreasing NF, which also provided inspiration for our subsequent research.…”
Section: Deep Fertilization Decreased Nitrogen Footprintmentioning
confidence: 99%
“…Deep fertilization is considered an effective method to ensure adequate nutrient supply during crop growth through precise fertilization at the roots of crops [7]. Deep fertilization promotes the absorption of soil nutrients by roots and reduces soil nutrient content [8]. It has advantages in improving fertilizer utilization efficiency, reducing greenhouse gas emissions, increasing crop yield, and improving economic benefits [9].…”
Section: Introductionmentioning
confidence: 99%
“…The soil total carbon (TC) and TN were measured using an EA3000 elemental analyzer (Eurotech Co., Ltd., Amaro, Italy). Soil NO 3 − -N and NH 4 + -N were measured using a SmartChem 200 discrete autoanalyzer (Alliance Co., Frepillon, France) based on the process described by Zheng et al [2]. The soil total potassium (TK) and AK were measured using flame photometry [33].…”
Section: Soil Sampling and Analysesmentioning
confidence: 99%
“…Nitrogen (N) plays a crucial role in maintaining and improving crop yields, and a large amount of N fertilizer is used in farmland systems every year [1,2]. Although the application of N fertilizer has increased crop productivity, it has also caused serious soil structure and quality degradation problems for arable land [3].…”
Section: Introductionmentioning
confidence: 99%